The effect of different fertilizer treatments on the sulphur and protein content of wheat - Burján, Zita Kata; Győri, Zoltán (Acta Agraria Debreceniensis, 2012)
In this study the effect of N,P and K nutrients on the S and protein content of wheat grains was investigated in a long-term fertilization experiment set up in Nagyhörcsök. The calcareous chernozem soil having the following characteristics: pH (KCl): 7.3, CaCO3: 4.27%, humus: 3.45%, Al-soluble P2O5 and K2O: 60–80 and 180–200, KCl- Mg: 150–180, KCl+EDTA-soluble Mn-, Cu- and Zn-content: 80–150, 2–3 and 1–2 mg kg-1. The experiment had a split-split-plot design with 40 treatments in 4 replications. Plant samples were collected from 2002 and 2004. 2002 was a drought year while 2004 was very wet. The main conclusions are as follows: – The sulphur and protein content were than the control higher in every NPK treatments. – The sulphur and protein content of the wheat grains were higher in 2004 that had a lot of rain than in 2002 that had drouht.